Gender equity and business leadership in the South African Mining sector - Boodhram, Farana (Department of Chemical Engineering, 2024)
Despite existing legislation and frameworks that are intended to protect women's rights, women remain under-represented in all aspects of the mining sector. Although scholarship has engaged with the challenges of women in the workplace across a wide range of contexts, it has not yet specifically addressed the challenges and possible opportunities in specific relation to women in business in the mining industry. The industry has the potential to rectify some of the gender equity issues by creating business leadership opportunities for women. This study therefore explores ways to achieve this gender equality in South Africa's mining industry by identifying ways of empowering women in the business of mining. The research questions sought to explore: 1) What is the current landscape of women participating in the business side of the mining industry in South Africa? 2) What are the key barriers and drivers with respect to improving participation of women in the business of mining? 3. What needs to change to bring more women into business in the mining industry? A grounded theory approach was considered most appropriate for this research because it draws on the lived experiences of participants, both female and male, occupying a wide range of leadership and management positions. Expert interviews with high profile leaders were selected as the best research method because of the value to be gained from their varied perspectives. The research indicated that the historic, systemic exclusion of women has resulted in cultural exclusion. To participate in the business of mining, women have had to integrate into the prevailing male-dominant culture. Not only has this prevented the full inclusion and participation of women but the industry has failed to harness the benefit of diversity. The research makes clear the challenges that women face in this industry; the findings can form the basis for new strategic and economic opportunities, a priority for the mining sector. The value of these research outcomes extends beyond the mining industry into the broader context of gender equity in business leadership. Actions taken on the research insights can positively address economic growth, private and public sector performance and income inequality. Together, these strategies have the potential to promote gender equality and create an environment which enables women's greater participation and advancement in the business of mining, and beyond.